Application of Linear Programming in Profit Maximization: A Case Study of Crunches Fried Chicken at Miami Tours and Travel Hotel in Kabale District. - Tayebwa, Osbert (Kabale University, 2023)
This project utilized the concept of simplex method algorithm; an aspect of linear programming to allocate raw materials to complete variables. The decision variables in the project work are the three different sizes of fried chicken on (tomatoes, onions and cooking oil) used in the production of fried chicken and amount of raw materials required for each variable. It was observed that big fried chicken should be produced because it contributed objectively to the profit of the hotel. V